Bronchorrhoea in a case of alveolar cell carcinoma. Issue 1 (January 1975) - Spiro, S G; Lopez-Vidriero M-T,; Charman, J; Das, I; Reid, L
Abstract : In a case of bronchorrhoea associated with alveolar cell carcinoma thf rheological and chemical features of the sputum indicated that it was bronchial fluid and not saliva and part bronchial secretion, partly serum transudate. The viscosity and chemical constituents were similar to those found in bronchorrhoea when associated with chronic bronchitis, asthma, or bronchiectasis. The surfactant studies suggested an alveolar origin for most of thf fluid, while the failure of fluid restriction, corticosteroids, atropine, or cytotoxic drugs to influence the sputum volume and properties indicated that the cells responsible are "autonomous".